A study on clinical manifestations and outcome of tuberculous meningitis among children with reference to BCG vaccination status and nutritional status - Dr. Srinivasa Arer; Dr. Vasundara S. Gayakwad (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Childhood tuberculosis is largely underestimated due to diagnostic difficulties and non-specific clinical manifestations, even in many tertiary care hospitals. With increase in coverage of BCG vaccination and improved nutritional status in children, modified clinical pictures of childhood tuberculous meningitis (TBM) has been observed in some research studies. Objectives: To study the different clinical manifestations and outcome of TBM in relation to BCG vaccinated, non- vaccinated and nutritional status of the children, in VIMS Bellary. Methodology: This is a case series prospective study. Patients admitted in the paediatric emergency ward from Nov 2003 to Nov 2004 were recruited for the study. The patients were classified according to their immunization status and nutritional status. Results: TBM constituted 29% of the total admitted TB cases. Majority were below 5 years. Fever, vomiting, positive McEwan’s sign and meningeal irritation signs were the commonest features observed. Atypical features were present in one third of the cases. No significant differences were seen between vaccinated and non-vaccinated patients. Significant differences, however, were observed in the clinical features and mortality between severely malnourished and well-nourished TBM cases in this study. Conclusion: It was concluded that clinical patterns in TBM vary according to nutritional status of the child and severe malnutrition carry very poor prognosis. Knowing different clinical patterns of the disease helps in early prognosis and thus in preventing deaths due to TBM among children.